Hubungan Motivasi Belajar dengan Academic Resilience pada Mahasiswa Pendidikan Agama Islam - Lila Suci Alfika; Raudhatul Jannah; Siti Zahwa Fadhilla; Surawan Surawan (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2026)
This study aimed to determine the relationship between learning motivation and academic resilience among students of the Islamic Education Study Program at UIN Palangka Raya. The research employed a quantitative approach with a correlational survey design. The population consisted of 50 students, while the sample involved 40 students selected through simple random sampling. Data were collected using a Likert-scale questionnaire consisting of 30 statement items, including 15 items measuring learning motivation and 15 items measuring academic resilience. The research instruments were tested for validity and reliability, resulting in Cronbach’s Alpha values of 0.872 for the learning motivation variable and 0.861 for the academic resilience variable, indicating that all items were valid and reliable. Data analysis was conducted using descriptive statistics, the Kolmogorov-Smirnov normality test, and Pearson Product Moment correlation analysis. The results showed that students’ learning motivation was categorized as very high with a percentage of 80%, while academic resilience was categorized as high with a percentage of 79%. The correlation test revealed a positive and significant relationship between learning motivation and academic resilience, with a correlation coefficient of 0.648 and a significance value of 0.000 < 0.05. These findings indicate that higher learning motivation is associated with higher academic resilience in facing academic pressures and challenges. This study confirms that learning motivation plays an important role in strengthening the academic resilience of Islamic Education students.